Kohler's Disease: Acute Foot Pain and Limping in Pediatric Emergency Department - Anıl Er; Murat Celal Sözbilen; Secil Kantas; Ezgi Oguz; Aykut Çağlar; Hurşit Apa (Trends in Pediatrics)
Kohler’s disease is a rare cause of limping in children which is hypothetically related with impaired blood supply of navicular bone by the compression of other tarsal bones. The clinical manifestations are pain and swelling in the midfoot and limping with typical steps on the lateral aspect of affected foot. As it is an elusive entity for physicians, the lack of clinical suspicion leads to utilization of advanced diagnostic tools and delayed diagnosis. Here we present a case of Kohler’s disease as a 5 years-old girl with acute foot pain and limping.